2009
DOI: 10.1182/blood-2009-02-203638
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish kidney stromal cell lines support multilineage hematopoiesis

Abstract: Studies of zebrafish hematopoiesis have been largely performed using mutagenesis approaches and retrospective analyses based upon gene expression patterns in whole embryos. We previously developed transplantation assays to test the repopulation potentials of candidate hematopoietic progenitor cells. We have been impaired, however, in determining cellular differentiation potentials by a lack of short-term functional assays. To enable more precise analyses of hematopoietic progenitor cells, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 54 publications
3
109
0
Order By: Relevance
“…WKM cells were prepared as described previously 49 . The cell suspension (5-8 Â 10 5 ml À 1 in PBS) of WKM was labelled with 5 mM of CellTracker Red CMTPX (Invitrogen) in PBS at 32°C for 15 min, then washed several times in the zebrafish culture media previously reported by Stachura et al 50 , then incubated at 32°C for another 40 min to release excess CMTPX. Stained cells were prepared in the zebrafish culture media at a concentration of 5 Â 10 7 ml À 1 for the transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…WKM cells were prepared as described previously 49 . The cell suspension (5-8 Â 10 5 ml À 1 in PBS) of WKM was labelled with 5 mM of CellTracker Red CMTPX (Invitrogen) in PBS at 32°C for 15 min, then washed several times in the zebrafish culture media previously reported by Stachura et al 50 , then incubated at 32°C for another 40 min to release excess CMTPX. Stained cells were prepared in the zebrafish culture media at a concentration of 5 Â 10 7 ml À 1 for the transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of immature hemoglobin-generating erythroblasts, as determined by differential cell counts and identified by o-dianisidine staining and MGG staining, indicated that the liver is the predominant site of erythropoiesis in adult X. laevis (Table1). There was no sign of hematopoiesis in the kidney, which serves as an important site of erythropoiesis in fish (Stachura et al, 2009).…”
Section: Presence Of Epor-positive Cells In the Hepatic Sinusoidmentioning
confidence: 95%
“…by guest www.bloodjournal.org From expressed highly in the kidney, the main site of hematopoiesis in adult teleosts 33 ( Figure 2C), and fractionation of WKM by light scatter characteristics 31 indicated that gcsfr was highly expressed in mature myeloid cells. Additionally, gcsfr was expressed in the "precursor" population, likely because of the presence of myeloid progenitors in this scatter fraction, 26,27 including putative common myeloid progenitors and granulocyte-monocyte progenitors. 34 gcsfr was also detected in the spleen and skin, likely because of the presence of neutrophils.…”
Section: Identification Of Gcsfbmentioning
confidence: 99%